2014
DOI: 10.1002/clen.201300453
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Fenton Oxidation of Salicylic Acid from Aqueous Solution: Batch Studies and Degradation Pathway

Abstract: This study investigated the removal of salicylic acid (SA) from aqueous solution by electro-Fenton (EF) and EF-like processes using graphite-graphite electrolytic system. Fe 0 , Fe 2þ , Fe 3þ ions were used as the Fenton reagent in the EF process and in the EF-like reactions, Cu 2þ , Mn 2þ , Ni 2þ were used as the same. The effect of various operating conditions on the effectiveness of EF process was investigated. The contribution of adsorption and electrosorption in the removal of SA was also investigated. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 62 publications
3
14
0
Order By: Relevance
“…The main aim of this work is to study the feasibility of commercially available graphite as both electrodes in EF process. Our previous studies reported that the graphitegraphite EF system is an efficient electrolytic system for the removal of dyes [39][40][41] and salicylic acid [32,33] from aqueous solution and the advantage of graphite-graphite EF process was reported in our previous work [39]. But, a detailed investigation of enhancement in dye removal efficiency of graphite-graphite EF system with the addition of NaHCO 3 was not studied in detail in any one of the articles.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The main aim of this work is to study the feasibility of commercially available graphite as both electrodes in EF process. Our previous studies reported that the graphitegraphite EF system is an efficient electrolytic system for the removal of dyes [39][40][41] and salicylic acid [32,33] from aqueous solution and the advantage of graphite-graphite EF process was reported in our previous work [39]. But, a detailed investigation of enhancement in dye removal efficiency of graphite-graphite EF system with the addition of NaHCO 3 was not studied in detail in any one of the articles.…”
Section: Introductionmentioning
confidence: 85%
“…Since, OH Å is the second strongest oxidant known after fluorine and has a very high standard potential, it will non-selectively react with the organic pollutants, leading to its complete mineralization [21]. EF process was successfully applied for the degradation and removal of dyes [22][23][24][25][26], pesticides and herbicides [27][28][29], phenolic compounds [30][31][32][33], leachate [34], drugs [35,36], aniline [37], petrochemical wastewater [38] etc.…”
Section: Introductionmentioning
confidence: 99%
“…While the former species can be degraded by • OH in the bulk, the latter ones are more refractory. The quick photolysis of Fe(III)-carboxylate species, primarily of the major Fe(III)-oxalate complexes, under UVA light or sunlight in PEF or SPEF, respectively, explains the better performance of these methods in decontamination of water with pharmaceuticals [22,41]. The addition of Cu 2+ as co-catalyst in EF and PEF accelerates the destruction of carboxylic acids due to the parallel destruction of Cu(II)-carboxylate species [31].…”
Section: Use Of Hplc Ic and Toxicity Analysis To Clarify The Reactivmentioning
confidence: 97%
“…When the drug contains N atoms, oxamic acid coming from the degradation of N-derivatives (e.g. acetamide) may also be formed [22,31,37,41]. Oxalic, oxamic and formic acids are directly converted into CO2 [7].…”
Section: Use Of Hplc Ic and Toxicity Analysis To Clarify The Reactivmentioning
confidence: 99%
See 1 more Smart Citation